BUILDING STUDENTS’ CHARACTER THROUGH MAIN CHARACTERS IN THE NOVEL KOOONG BY IWAN SIMATUPANG - Haryadi Haryadi (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
The purpose of this paper to illustrate the main character in the novel Kooong by Iwan Simatupang to build the character of students. This is a qualitative study using content analysis method. Design research is asking questions, collecting data, and interpreting the data. This study uses two structural approach and the approach of psychoanalysis Sigmund Freud. Results of the study: (1) The structure of the novel Kooong: (a) the theme of human wanderings; (b) a flashback; (c) the background in Jakarta and Central Java; (d) the main character Mr. Sastro; and (d) third-person point of view with her style omniscient. (2) psychological disturbances: (a) the form of psychological disorders: depression and schizophrenia. (b) the causes of mental disorders: loss of turtledoves, children, and his wife. (c) due to mental disorders: a grumpy, left the village, and is considered crazy. (d) solution psychological disorders: submission to God and give a message to Mr. Headman and his friends throughout the village. Keywords: building character, learners, the main character, novel